Geography, Industrial Organization, and Agglomeration - Rosenthal, Stuart S.; Strange, William C. (The Review of Economics and Statistics, 2003)
This paper makes two contributions to the empirical literature on agglomeration economies. First, the paper uses a unique and rich database in conjunction with mapping software to measure the geographic extent of agglomerative externalities. Previous papers have been forced to assume that agglomeration economies are club goods that operate at a metropolitan scale. Second, the paper tests for the existence of organizational agglomeration economies of the kind studied qualitatively by Saxenian (1994). This is a potentially important source of increasing returns that previous empirical work has not considered. Results indicate that localization economies attenuate rapidly and that industrial organization affects the benefits of agglomeration.